Graphene Fiber‐Based Wearable Supercapacitors: Recent Advances in Design, Construction, and Application. Issue 9 (16th August 2021) - Cheng, Hengyang; Li, Qing; Zhu, Liangliang; Chen, Su
Abstract: Fiber‐based supercapacitors (FSCs) that display small volume, robust weavability, high power density, and long‐term stability, have urgently become the indispensable power supplies in smart wearable industries. Graphene fiber is regarded as an ideal FSCs electrode due to its remarkable natures of anisotropic framework, adjustable layer spacing, porous structures, large specific‐surface‐area, processable electroactivity, and high electronical and mechanical properties. This review, mainly focuses on the graphene fiber‐based supercapacitors (GFSCs), with respect to fiber preparation, micro‐nanostructure modulation, supercapacitor construction, performance optimization, and wearable applications. Various fiber fabrication strategies, including wet‐spinning, dry‐spinning, film conversion, confined hydrothermal self‐assembly, and microfluidic‐spinning are presented for fiber's structure manipulation and large‐scale production. Advanced nanostructures and electroactivity with various building principles, such as oriented alignment, porous network, hierarchical, and heterogeneous skeleton, engineered active‐sites, and mechanical regulation are discussed for boosting charge transfer, and ionic kinetic diffusion and storage. Especially, the optimizing approaches for regular unit alignment, enhanced interlayer interactions, modulated structural nano‐architecture are presented to deliver high capacitance and energy density. Moreover, the flexibility and stretchability of graphene fiber, together with wearable applications of power supply are highlighted. Finally, a short summary, current challenges and future perspectives for designing high energy density GFSCs are proposed. Abstract : In this review, the advanced progress in graphene fiber‐based flexible supercapacitors is comprehensively summarized, mostly focusing on the fiber preparation and morphology modulation methodologies, critical parameters of supercapacitors, charge storage mechanisms, structure‐activity relationship, key structural characteristic for superior mechanical/electrical properties, optimized strategies for high capacitance performance, constructions of supercapacitor, and practical wearable applications.